Managers' information literacy: a case study of a cluster in Brazil - Capinzaiki Ottonicar, Selma Leticia [UNESP]; Pomim Valentim, Marta Ligia [UNESP]; Feres, Gloria Georges [UNESP] (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2018)
Introduction: Managers need to be information literate to take effective decisions. Objectives: This study aims to analyze the situation of information literacy in small businesses organized as clusters and develop a case study about the electronics industrial cluster in the city of Garca, Sao Paulo State. Method: A literature review supported the elaboration of theory about information literacy; documentary research to characterise the historical research universe; and a case study, covering a set of eleven (11) small companies in the electronics sector. Results: The managers value information, knowledge and lifelong learning. However, they do not understand that information literacy influences competitive advantage. The results demonstrate that information literacy is an influential factor in the business competitiveness of these organizations and therefore effectively contributes to the survival of companies in the market. Information literacy contributes directly to small businesses' growth organized as a cluster. Conclusions: Managers rely on a group to share information. Furthermore, they evaluate information to create innovation through creativity.
Keywords: Information Literacy; Cluster; Small Businesses; Competitiveness; Lifelong Learning; Electronic Industry